Sociology of Pandemics A Sociological Approach to Understanding the Social Impacts of COVID- 19 - Abdelghani, Hosni Ibrahim (Journal of Ecohumanism, 2025)
There is no doubt that there is a social and ethical necessity to monitor the various aspects of this pandemic, and to reveal its effects on the social reality in its various aspects, and thus the results of the study can be used to develop a scientific plan to limit the spread of the pandemic, and there is no doubt that This contributes to creating a safe social environment capable of responding to all social and economic development programs. The Sane Society is the society that is most capable of change and development in all fields. The study problem is determined in revealing the sociological approach to the Corona pandemic, identifying its various dimensions, and monitoring the sociological effort in revealing its most prominent results and its various effects on some social systems. The study uses the Discourse Analysis method, where the study aspires to analyze an aspect of the Arab and Western sociological discourse related to the Corona virus, and to identify the extent to which this discourse monitors the effects of that epidemic.